2016
DOI: 10.1083/jcb.201602064
|View full text |Cite
|
Sign up to set email alerts
|

A family of membrane-shaping proteins at ER subdomains regulates pre-peroxisomal vesicle biogenesis

Abstract: Joshi et al. show that Pex30p and Pex31p contain reticulon-like ER tubulating domains. Like reticulons, they localize to the edges of ER sheets and tubules but are only present in subdomains. These subdomains are devoid of reticulons and are the sites of pre-peroxisome vesicle biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(133 citation statements)
references
References 51 publications
(84 reference statements)
8
125
0
Order By: Relevance
“…Endoplasmic reticulum proteins implicated in the regulation of in vivo peroxisome reintroduction include the reticulon homology domain-containing proteins (RHPs) Rtn1, Rtn2, and Yop1 as well as the ER-localized peroxins Pex29, Pex30, and Pex31. The absence of RHPs speeds up peroxisome formation, pointing to a role of ER architecture in this process [43][44][45]. Conversely, reappearance of peroxisomes is slowed down by the absence of Pex30 or Pex31 [45].…”
Section: Peroxisomal Membrane Structures Do Exist In Yeast Pex3 and Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoplasmic reticulum proteins implicated in the regulation of in vivo peroxisome reintroduction include the reticulon homology domain-containing proteins (RHPs) Rtn1, Rtn2, and Yop1 as well as the ER-localized peroxins Pex29, Pex30, and Pex31. The absence of RHPs speeds up peroxisome formation, pointing to a role of ER architecture in this process [43][44][45]. Conversely, reappearance of peroxisomes is slowed down by the absence of Pex30 or Pex31 [45].…”
Section: Peroxisomal Membrane Structures Do Exist In Yeast Pex3 and Pmentioning
confidence: 99%
“…The absence of RHPs speeds up peroxisome formation, pointing to a role of ER architecture in this process [43][44][45]. Conversely, reappearance of peroxisomes is slowed down by the absence of Pex30 or Pex31 [45]. In vitro vesicle budding assays using permeabilized S. cerevisiae pex19 cells revealed that in the absence of RHPs, Pex29, or Pex30, the release of Pex3 is enhanced [43].…”
Section: Peroxisomal Membrane Structures Do Exist In Yeast Pex3 and Pmentioning
confidence: 99%
“…In S. cerevisiae and humans, independent studies suggest that Pex3, and in yeast probably Pex13 and Pex14 as well, insert into the ER, post-translationally via the Sec61 translocon [1012]. In the same yeast, two ER-resident peroxins, Pex30 and Pex31, contribute to the generation of the pER [13]. In Komagataella phaffii (formerly called Pichia pastoris ), two intra-ER sorting routes to the pER are described [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our goal was to correlate changes in Inp1p's protein interactions with phenotypic changes observed in the inp1 mutant strains. Interactions of Inp1p with the following proteins were systematically queried by yeast 2‐hybrid (Y2H) analysis: Pex3p, which has previously been described as crucial for foci formation and peroxisome tethering; Atg36p, which has been implicated in peroxisome degradation; Pex30p, an integral membrane protein that also interacts with reticulons to regulate peroxisome biogenesis at the ER; Vam6p, a member of the HOPS tethering complex that has recently been implicated in mitochondria‐vacuole tethering; Pex25p, a protein involved in peroxisome division; Cdc3p, a septin that has been implicated as an interaction partner of Inp1p; and Pex17p, a member of the peroxisomal importomer complex that has recently been identified as an Inp1p‐interacting protein . A heat map depicts the strengths of interaction of wild‐type Inp1p and of 14 Inp1p point mutants with these 7 Inp1p interacting proteins in Y2H assays (Figure A).…”
Section: Resultsmentioning
confidence: 99%